Evaluasi Sistem Informasi Manajemen Dokumen Akreditasi (SISMADAK) Dengan Menggunakan Metode PIECES di Rumah Sakit Bhayangkara Lumajang - Ines Meiyola Pradanthi; Feby Erawantini; Sustin Farlinda; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2020)
Bhayangkara Hospital Lumajang is one of SNARS accredited health agencies and SISMADAK is used in the reporting process to KARS. The problems is still found in its application, which resulted in staff being less satisfied with SISMADAK. The aims of this study was to evaluate SISMADAK in terms of user satisfaction using the PIECES method. The study was quantitative descriptive study, which is described as a descriptive evaluation by comparing user satisfaction with information systems. The result of description evaluate of SISMADAK using PIECES method in Bhayangkara Hospital Lumajang about satisfaction percentage found 81% of performance variable was showed very good, 81% of information variable was stated very good, 69% of economic variable was good, 76% control variable was stated very good, 70% of efficiency variable was stated very good, and 80% of service variable was responded very good. For further advices were the planned of SISMADAK users need related information that is not yet available, beside the staff should increase the confidentiality of data on SISMADAK. The conclusion of this study is SISMADAK able to facilitate users in the hospital accreditation process of KARS.